Strategi Komunikasi PT Angkasa Pura I (Persero) Cabang BIL dalam Penertiban PKL di Bandara Periode Oktober 2011 â Mei 2014 (Studi Kasus Upaya Penertiban Pedagang Kaki Lima di Bandara Internasional Lombok) - , Lale Fitria Ariyani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
People euphoria in welcoming the operation of Lombok International Airport is magnificent. This euphoria is in contrary with the interest of PT Angkasa Pura I (Persero) of BIL branch to bring its vision and mission into reality, which is to become one of the best ten airport organizing companies in Asia. Realizing that street vendorsâ phenomenon may bring some negative impacts towards the company, thus many enforcement efforts are taken. The formulation of study explains the communication strategy taken by PT Angkasa Pura-I (Persero) of BIL branch in disciplining street vendors (PKL) in Lombok International Airport (BIL). This study is purposed to analyze communication strategy used by PT AP-I (Persero) Cabang BIL for disciplining street vendors (PKL) in Lombok International Airport and to investigate until to which extent persuasive method can change their opinion, attitude and behavior. Ituses the theory of Strategic Contingence for Organizational Communication from Garnet. Then, this writing is focused more on corporate communication as the extension of Public Relationâs function. The analysis adapts and develops Strategic Contingence for Organizational Communication from Garnett. The author uses qualitativedescriptive method with case study, which referred to intrinsic case study. The results of this study are as follows: Street vendors are insisted to trade inside of the airportâs area because they hold the government promises to raise the prosperity of community around the airportâs area. To this matter, a corporate communication strategy for disciplining street vendors in the airport area must be supported by action strategy. Although street vendors showed a more cooperative response with the company, it can be seen from their willingness to be relocated into a new place, until this study is over, however, there are still many disordered activities showed by them. This is due to unprepared relocation area for them. This fact showed that street vendorsâ matter in BIL is not only related to the communication problem, but also community demand to the fulfillment of their livelihood. Thus, it can be concluded that the communication strategy taken by PT AP-I is only limited on raising awareness from street vendors to be more orderly behaved according to the prevailed regulation. Street vendorsâ phenomenon in BIL after relocation and âberatongâ phenomenon, especially related to persuasive strategy taken by PT AP-I, has educated local community to be more orderly behaved based on the symbols found in the airport